2000
DOI: 10.1177/026835550001500102
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Chronic Venous Diseases

Abstract: Objective: To review the prevalence of and risk factors for varicose veins, chronic venous insufficiency (CVI) and venous leg ulcers. Data sources: MEDLINE was searched for the terms prevalence and varicose veins, chronic venous insufficiency, or venous leg ulcers. Study selection: The extant world literature (1966–1999) with a minimum of an available English abstract was collected. Ninety-nine studies were reviewed. Data extraction: Data were extracted on prevalence of diseases of the veins in the lower limb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 66 publications
0
24
2
1
Order By: Relevance
“…The prevalence of venous disease increases with age. 13 Varicose veins are a known occupational disease, found in people required to stand for prolonged periods. We found that our study had 47.14% farmers, who admitted that their occupation required standing for long intervals.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of venous disease increases with age. 13 Varicose veins are a known occupational disease, found in people required to stand for prolonged periods. We found that our study had 47.14% farmers, who admitted that their occupation required standing for long intervals.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to reduce but not eliminate this potential bias, and it is well recognized that if researchers rely on patient self-report, it can generate a high rate of false positives and lead to a gross overestimation of prevalence [19,20]. In the experience of the authors, reliance on selfreport in a study of foot ulcer prevalence would have led to an overestimation of point prevalence by 17% and overall prevalence by as much as 27% [7].…”
Section: Discussionmentioning
confidence: 99%
“…La enfermedad venosa de las extremidades inferiores es la enfermedad vascular más frecuente 14 , representando la mayor prevalencia la insuficiencia venosa crónica superficial de la vena safena interna o externa. Sin desconocer el peligro de eventos trombóticos, aparición de úlceras, eccema o episodios de varicorragia, muchas veces la enfermedad venosa es considerada un mero problema estético desconociendo los efectos en la calidad de vida de los pacientes que sufren dolores y molestias, limitaciones en las actividades cotidianas y sociales, y en su imagen corporal y autoestima personal.…”
Section: Comentariounclassified